(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article examines the pedagogical, psychological, and developmental significance of using fairy tale therapy in preschool educational institutions. Fairy tale therapy is considered an effective method for improving children’s emotional well-being, developing imagination, overcoming fears, and forming social skills. The paper analyzes theoretical foundations, methodological approaches, and the practical value of therapeutic storytelling within modern early childhood education.